Structural trends of the peasantry in Peru - Jurado, Joel (1989)
Today there is a tendency to question the political validity of the popular social classes, as it is argued that new actors have entered the social scene displacing them from the expected role in the transformation of our societies. Thus, in Peru it is repeatedly argued that the social agents that are causing the greatest changes are no longer precisely the conventional popular classes, but rather social sectors such as the urban poor, state workers, women, youth, migrants, regional movements, among others.